2010
DOI: 10.3171/2009.7.spine08589
|View full text |Cite
|
Sign up to set email alerts
|

Anterior fixation of odontoid fractures in an elderly population

Abstract: Object Fractures of the odontoid process are the most common fractures of the cervical spine in patients over the age of 70 years. The incidence of fracture nonunion in this population has been estimated to be 20-fold greater than that in patients under the age of 50 years if surgical stabilization is not used. Anterior and posterior approaches have both been advocated, with excellent results reported, but surgeons should understand the drawbacks of the various techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
88
1
10

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 114 publications
(101 citation statements)
references
References 66 publications
2
88
1
10
Order By: Relevance
“…However, this study did not address the BMD of the specimen and thus, the relevance of this study for elderly patients with poor bone quality remains questionable. Dailey et al [28] recently found significantly increased union rates in elderly patients using a two-screw construct and also our results, though not significant (P = 0.06) indicated similar. A remarkable finding of our study was a significant higher union rate through an increased fracture footprint, explainable through the endostal healing process of the odontoid, and explaining higher healing rates of Type III OF.…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…However, this study did not address the BMD of the specimen and thus, the relevance of this study for elderly patients with poor bone quality remains questionable. Dailey et al [28] recently found significantly increased union rates in elderly patients using a two-screw construct and also our results, though not significant (P = 0.06) indicated similar. A remarkable finding of our study was a significant higher union rate through an increased fracture footprint, explainable through the endostal healing process of the odontoid, and explaining higher healing rates of Type III OF.…”
Section: Discussionsupporting
confidence: 80%
“…In light of the existing literature without clear evidence for a preferable technique [18,22,25,28,34,43,[60][61][62], the decision regarding the number of screws in our cohort was taken by the surgeon depending on individual preference. Bohler [13] advocated a two screw fixation, thus theoretically increasing rotational stability and construct strength.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations